Black mulberry (Morus nigra) fruit extract alleviated AD-Like symptoms induced by toxic Aβ protein in transgenic Caenorhabditis elegans via insulin DAF-16 signaling pathway. (October 2022) - Wang, Enhui; Wang, Ningbo; Zou, Yue; Fahim, Muhammad; Zhou, Yongtao; Yang, Hui; Liu, Yan; Li, Hongyu
Graphical abstract: Highlights: First time reported that MF has potiential function in AD treatment. MF effectively alleviated the AD-like toxic symptoms induced by Aβ1-42 in C. elegans . MF exerted anti-AD action by the DAF-16 pathway and activated antioxidant-related sod-3 and gst-4 to improve antioxidant capacity in C. elegans. MF can prolong the lifespan of C. elegans . Abstract: Alzheimer's disease (AD) is one of the most severe neurodegenerative disorders. Recently, there is no effective treatment drug for AD. Morus nigra ( M. nigra ) is a black mulberry and widely distributed fruit in the Moraceae family with various undiscovered biological activities. The study aimed to investigate the potential anti-AD effect of M. nigra . Mulberry fruit extract (MF) was obtained from M. nigra and treated up to 1.00 mg/mL on transgenic AD Caenorhabditis elegans ( C. elegans ) models. MF inhibited Amyloid-β (Aβ)-induced paralysis symptoms by about 55.65 %, reduced Aβ accumulation more than 50 % via immunoblotting, and suppressed over-sensitivity to exogenous serotonin in C. elegans . Furthermore, MF decreased the Aβ oligomeric depositions in worm CL2006. MF activated the DAF-16 nuclear translocation and its downstream SOD-3 and GST-4. AD is a major age-related disorder. Therefore, MF treated for an aging test and proved to be expanded the lifespan of the worms up to 34.7 %. Besides, we have evaluated the MF in vivo antioxidative properties, where MF reduced reactive oxygen species (ROS) generations in C. elegans and remitted the activation of HSP-16.2 induced by the oxidative action of Juglone. Gene knockout and extended the lifespan of AD worms. However, RNA interference (RNAi) successfully silenced the daf-16 on the Aβ phenotypic paralysis proved by MF effect. Our results indicate that MF alleviates AD-Like symptoms by activating the DAF-16 insulin signal pathway in C. elegans . Therefore, this MF study may provide new insights for mulberry application in safe AD treatment and clinical study.